Photometric analysis and evolutionary stages of the contact binary V2790 Ori - Wichean Kriwattanawong (2020)
© National Astronomical Observatories, CAS and IOP Publishing Ltd.. A photometric analysis and evolutionary stages of the contact binary V2790 Ori are presented. The BVR C observations were carried out at the Thai National Observatory. The photometric light curves were fitted to provide fundamental parameters, required to examine evolutionary stages of the binary. The results indicate that V2790 Ori is a W-type contact system with a mass ratio of q = 2.932. The orbital period increase is found at a rate of dP/dt = 1.03 × 10-7 d yr-1. This implies that a rate of mass transfer from the secondary component to the primary one is dm 2/dt = 6.31 × 10-8 M o yr-1. Furthermore, we find that from the detached phase to the contact phase, the amount of mass that the evolved secondary component has lost is 1.188±0.110 M o, i.e., mass lost by the system is 0.789±0.073 M o and mass transfer to the primary is 0.399±0.037 M o. Since the time of the first overflow, the angular momentum loss is found to be 72.2% of J FOF, causing the orbit and Roche surface to shrink until the present time.